The Oweniidae (Annelida; Polychaeta) from Lizard Island (Great Barrier Reef, Australia) with the description of two new species of Owenia Delle Chiaje, 1844 - Parapar, Julio; Moreira, Juan (Zootaxa, 2015)
Study of the Oweniidae specimens (Annelida; Polychaeta) from Lizard Island (Great Barrier Reef, Australia) stored at the Australian Museum, Sydney and newly collected in August 2013 revealed the presence of three species, namely Galathowenia quelis Capa et al., 2012 and two new species belonging to the genus Owenia Delle Chiaje, 1844. Owenia dichotoma n. sp. is characterised by a very short branchial crown of about 1/3 of thoracic length which bears short, dichotomously-branched tentacles provided with the major division close to the base of the crown. Owenia picta n. sp. is characterised by a long branchial crown of about 4/5 of thoracic length provided with no major divisions, ventral pigmentation on thorax and the presence of deep ventro-lateral groove on the first thoracic chaetiger. A key of Owenia species hitherto described or reported in South East Asia and Australasia regions is provided based on characters of the branchial crown.